Modular prosthetic reconstruction for primary bone tumours of the distal tibia in ten patients - Mugla, Walid (Division of General Surgery, 2023)
Introduction: Below knee amputation is the safest treatment for aggressive benign and malignant bone tumours of the distal tibia yielding good oncological and functional results. However, in selected patients where limb salvage is feasible and amputation unacceptable to the patient, limb salvage using a distal tibial replacement (DTR) can be considered. This study aims to present the oncological and functional results of the use of this treatment method in our unit. Patients & Methods: A retrospective folder review was performed for all 10 patients who received a modular distal tibial replacement between 01/01/2005 and 31/01/2019 for a primary bone tumour either benign aggressive or malignant. Six were female and the mean age was 31 (1275) years. There were five patients with giant cell tumour of bone, four with osteosarcoma and one with a low-grade chondrosarcoma. The patients with osteosarcoma had neo-adjuvant chemotherapy before surgery. Function was assessed by the Musculoskeletal Tumor Society (MSTS) score. Results: There were six females and four males, with a mean age of 31 (12-75) years. Two patients had local recurrence treated with a BKA and one other patient died of metastases three years postoperatively. At a mean follow-up of three years, the remaining eight patients had a mean MSTS score of 83% (67–93%). There were no radiological signs of loosening, and no revision surgeries. Conclusion: Endoprosthetic replacement of the distal tibia for primary bone tumours can be a safe treatment option in very selected cases.